IMPLEMENTASI NILAI KARAKTER NASIONALISME DAN GOTONG ROYONG DALAM KEGIATAN EKSTRAKURIKULER TARI REOG KENDANG PADA SISWA SDN 2 KEPATIHAN TULUNGAGUNG - Ria Fajrin Rizqy Ana Ria; Vava Adianto Kusuma (INVENTA: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
Character education is an effort to help the development of students both physically and psychically from their nature towards a better direction. The purpose of this study is to describe the application of Nationalist character education and Mutual Cooperation through extracurricular activities of Reog Kendang dance at SD Negeri 2 Kepatihan. The data collection techniques used in this study were interviews and documentation. The character values of nationalism and mutual cooperation in extracurricular activities of reog kendang dance in students at SDN 2 Kepatihan Tulumgagung in this study have been well achieved.